Molecular Heterogeneity of Endometrioid Ovarian Carcinoma: An Analysis of 166 Cases Using the Endometrial Cancer Subrogate Molecular Classification. (July 2020) - Leskela, Susanna; Romero, Ignacio; Rosa-Rosa, Juan M.; Caniego-Casas, Tamara; Cristobal, Eva; Pérez-Mies, Belén; Gutierrez-Pecharroman, Ana; Santón, Almudena; Ojeda, Belén; López-Reig, Raquel; Palacios-Berraquero, María L.; Andrada, Encarna; et al.
Abstract : Endometrioid ovarian carcinoma (EOC) has clinical and biological differences compared with other histologic types of ovarian carcinomas, but it shares morphologic and molecular features with endometrioid endometrial carcinoma. To analyze the molecular heterogeneity of EOC according to the new molecular classification of endometrial cancer and to evaluate the prognostic significance of this molecular classification, we have analyzed 166 early-stage EOC by immunohistochemistry for mismatch repair proteins and p53 expression, and by Sanger sequencing for the exonuclease domain of polymerase epsilon ( POLE EDM ). In addition, we have carried out next-generation sequencing analysis of tumors with POLE EDM mutations to confirm the ultramutated profile. Eight tumors carried POLE EDM mutations and were classified as ultramutated (5%), 29 showed mismatch repair deficiency and were classified as hypermutated (18%), 16 tumors had a mutated pattern of p53 expression and were classified as p53 abnormal (11%), and 114 tumors did not have any of the previous alterations and were classified as no specific type (66%). Five tumors showed >1 classification criteria. The frequencies of ultramutated and hypermutated tumors were lower in EOC compared with the frequency reported in endometrial cancer. Subrogate molecular groups differed in both morphologic features (histologic grade, squamous and morular metaplasia, and necrosis) and immunohistochemical expression of several biomarkers (ARID1A, nuclear β-catenin, estrogen receptors, Napsin A, and HINF1B). In addition, the number of CD8 + tumor-infiltrating lymphocytes was higher in ultramutated and hypermutated tumors. The most commonly mutated genes in the ultramutated group were ARID1A (100%), PIK3R1, PTEN, BCOR, and TP53 (67% each), whereas no mutations were detected in KRAS. Although the prognosis did not differ among subgroups in the multivariate analysis, a trend toward a better prognosis in POLE -mutated and a worse prognosis in p53 abnormal tumors was observed. In addition, this classification could have important therapeutic implications for the use of immunotherapy in tumors classified as ultramutated and hypermutated. Abstract : Supplemental Digital Content is available in the text.